2017
DOI: 10.3390/v9090247
|View full text |Cite
|
Sign up to set email alerts
|

SGS3 Cooperates with RDR6 in Triggering Geminivirus-Induced Gene Silencing and in Suppressing Geminivirus Infection in Nicotiana Benthamiana

Abstract: RNA silencing has an important role in defending against virus infection in plants. Plants with the deficiency of RNA silencing components often show enhanced susceptibility to viral infections. RNA-dependent RNA polymerase (RDRs) mediated-antiviral defense has a pivotal role in resistance to many plant viruses. In RDR6-mediated defense against viral infection, a plant-specific RNA binding protein, Suppressor of Gene Silencing 3 (SGS3), was also found to fight against some viruses in Arabidopsis. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 43 publications
2
40
1
Order By: Relevance
“…Since its discovery as a target for potyviral HC-Pro, additional studies show that rgsCaM-like proteins interact with multiple viral suppressor proteins from a wide array of plant viruses (Nakahara et al, 2012; Li et al, 2014; Yong Chung et al, 2014; Li et al, 2017). By using surface plasmon resonance analysis, (Nakahara et al, 2012) demonstrated the interaction of tobacco rgsCaM with the bromoviral suppressor of silencing 2b protein as well as other viral suppressors.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since its discovery as a target for potyviral HC-Pro, additional studies show that rgsCaM-like proteins interact with multiple viral suppressor proteins from a wide array of plant viruses (Nakahara et al, 2012; Li et al, 2014; Yong Chung et al, 2014; Li et al, 2017). By using surface plasmon resonance analysis, (Nakahara et al, 2012) demonstrated the interaction of tobacco rgsCaM with the bromoviral suppressor of silencing 2b protein as well as other viral suppressors.…”
Section: Introductionmentioning
confidence: 99%
“…A strong connection of rgsCaM to autophagy has been discovered by Li et al (2017), who demonstrated that the SGS3 protein encoded by SUPPRESSOR OF GENE SILENCING 3 is a direct interaction target for rgsCaM (Li et al, 2017). SGS3 is an RNA-binding homodimeric protein that forms a stable complex with RNA-dependent RNA polymerase 6 (RDR6).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations